Potential Role of CD47-Directed Bispecific Antibodies in Cancer Immunotherapy - Yang, Yan; Yang, Zheng; Yang, Yun (Frontiers in Immunology, 2021)
The prosperity of immunological therapy for cancer has aroused enormous passion for exploiting the novel targets of cancer immunotherapy. After the approval of blinatumomab, a bispecific antibody (bsAb) targeting on CD19 for acute lymphoblastic leukemia, a few of CD47-targeted bsAbs for cancer immunotherapy, are currently in clinical research. In our review of CD47-targeted bsAbs, we described the fundamental of bsAbs. Then, we summarized the information of four undergoing phase I researches, reviewed the main toxicities relevant to CD47-targeted bsAb immunological therapy of on-target cytotoxicity to healthy cells and a remarkable antigen-sink. Finally, we described possible mechanisms of resistance to CD47-targeted bsAb therapy. More clinical researches are supposed to adequately confirm its security and efficacy in clinical practice.